MENINGKATKAN KEAKTIFAN DAN KEMAMPUAN BERHITUNG MELALUI PEMBELAJARAN MAKE A MATCH SISWA KELAS 1 SDN 053 LARA III KECAMATAN BAEBUNTA SELATAN KABUPATEN LUWU UTARA - Rosa Delima; Maulidnawati Jumrah, Abrina; Erwin Nurdiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the activeness and numeracy skills of grade 1 students at SDN 053 Lara III through the application of the Make a Match learning model. This type of research is Classroom Action Research (CAR) conducted in two cycles. The research subjects were 22 grade 1 students, consisting of 7 male students and 15 female students. Data collection techniques used observation, tests, and documentation. The results showed an increase in student activeness and numeracy skills in each cycle. In cycle I, the percentage of student activeness reached 63.6% (quite active category) and numeracy skills obtained an average of 65.9 with classical completeness of 54.5%. In cycle II, student activeness increased to 86.4% (active category) and numeracy skills obtained an average of 80.5 with classical completeness of 86.4%. Thus, it can be concluded that the application of the Make a Match learning model can improve the activeness and numeracy skills of grade 1 students at SDN 053 Lara III.